PERAN PENYULUH PERTANIAN DALAM USAHATANI PADI SAWAH DI KELURAHAN HORODOPI KECAMATAN MOWEWE KABUPATEN KOLAKA TIMUR - Dirman Yulianto; Salahuddin Salahuddin; Yoenita Jayadisastra; Sitti Nur Isnian (Jurusan Penyuluhan Pertanian FP UHO, 2025)
This study aims to determine the role of agricultural extension workers in rice farming in Horodopi Village, Mowewe District, East Kolaka Regency. The population of this study consists of all rice farmers in the village, totaling 206 people. The sample size was determined using the Slovin formula with a 10% margin of error, resulting in 69 people. The sample in this study was taken using the simple random sampling method. The data collection techniques used in this study include documentation, interviews, and surveys using questionnaires. The research variable is the role of agricultural extension officers. The data were analyzed using quantitative descriptive analysis methods. The results of the study indicate that the role of agricultural extension officers in the village. The results of the study indicate that the role of agricultural extension workers in Horodopi Village, Mowewe District, is generally categorized as good in terms of their roles as facilitators, innovators, motivators, and educators. A total of 81.15% of respondents rated the role of extension workers as very good in supporting the process of rice farming. Extension workers are not only a source of information but also active companions who encourage farmers to adopt modern technologies such as the jajar legowo planting system, balanced fertilization, and the use of pest-resistant superior varieties. This success is supported by the extension workers' ability to build effective communication, understand local needs, and apply participatory methods that motivate farmers to be independent and innovative. The combination of their roles as facilitators, innovators, motivators, and educators significantly enhances farmers' productivity, participation, and well-being, while also providing a mentoring model that can be replicated in other agricultural areas to achieve sustainable rice farming.